2016
DOI: 10.1016/j.molonc.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

SNHG16 is regulated by the Wnt pathway in colorectal cancer and affects genes involved in lipid metabolism

Abstract: It is well established that lncRNAs are aberrantly expressed in cancer where they have been shown to act as oncogenes or tumor suppressors. RNA profiling of 314 colorectal adenomas/adenocarcinomas and 292 adjacent normal colon mucosa samples using RNA‐sequencing demonstrated that the snoRNA host gene 16 (SNHG16) is significantly up‐regulated in adenomas and all stages of CRC. SNHG16 expression was positively correlated to the expression of Wnt‐regulated transcription factors, including ASCL2, ETS2, and c‐Myc. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 67 publications
3
166
2
1
Order By: Relevance
“…For example, SNHG16 has been found to be up-regulated in colorectal cancers and affected the genes involved in lipid metabolism [15]. In a recent study, SNHG16 has been found to be overexpressed and contributed to the development of non-small cell lung cancer (NSCLC) via inhibition of miR-146a [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, SNHG16 has been found to be up-regulated in colorectal cancers and affected the genes involved in lipid metabolism [15]. In a recent study, SNHG16 has been found to be overexpressed and contributed to the development of non-small cell lung cancer (NSCLC) via inhibition of miR-146a [16].…”
Section: Discussionmentioning
confidence: 99%
“…57. The Anoikis resistance assay was performed with Corning Costar Ultra-Low attachment 24-well plates (Corning Life Science, Tewksbury, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Probably, the colorectal cancer cases contain mutated versions of XPOT that might lead to transfer of oncoproteins and ETC-1922159 might act as an inhibitor for mutated XPOT. SNHG16 (snoRNA host gene 16) has been demonstrated to be significantly up regulated in adenomas and all stages of CRC 206 . Christensen et al 206 report positive correlation with Wnt regulated factors like ASCL2 which is known for contributing to stemness.…”
Section: Dicationmentioning
confidence: 99%
“…SNHG16 (snoRNA host gene 16) has been demonstrated to be significantly up regulated in adenomas and all stages of CRC 206 . Christensen et al 206 report positive correlation with Wnt regulated factors like ASCL2 which is known for contributing to stemness. Also, silencing of SNHG16 has been found to affect lipid metabolism and increase apoptotic cell death.…”
Section: Dicationmentioning
confidence: 99%
See 1 more Smart Citation